Oleksandr Dovzhenko, Ivan Kavaleridze, Leonid Skrypnyk: The avant-garde and philosophical explorations of Ukrainian filmmakers of the 1920s - Naumova, Larysa (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The filmmakers Oleksandr Dovzhenko and Ivan Kavaleridze created bold avant-garde works at the time when Ukrainian cinema was being established, at the end of the 1920s and early 1930s. In effect, the works of these two directors shaped the defining features of Ukrainian cinema. This article discusses the creative methods used by Dovzhenko in his three films Zvenyhora (1927), Arsenal (1929) and Earth (1930), which clearly depict Ukrainian worldviews and mentality. Kavaleridze’s approach is considered in the light of two of his films, Downpour (1929) and Perekop (1930). Already a recognized sculptor at the time, Kavaleridze sought unique forms of expression in film. The approaches these directors took towards framing scenes, montage, lighting and rhythm underpinned the theoretical propositions of their contemporary, Ukrainian film theorist Leonid Skrypnyk. The author suggests that this testifies to a deliberate and comprehensive search for new means of expression in all phases of filmmaking.